(untitled) (Bangladesh Journal of Medical Science, 2024)
Background: Presently, transcutaneous determination of bilirubin has become a valuable method for the early detection of neonatal hyperbilirubinemia. This study aims to determine the correlation of transcutaneous bilirubin with serum bilirubin levels and assess the factors affecting transcutaneous bilirubin measurement in term and late preterm neonates. Materials and Methods: The study included 100 newborns born at a gestational age of 35 to 41 weeks, with a birth weight of 2100 to 3500 g. Simultaneous measurement of bilirubin by traditional (invasive) and transcutaneous (non-invasive) methods was carried out within 15 minutes of admission in the neonatal intensive care unit. Parallel transcutaneous measurements were taken in the forehead and sternum. Statistical analysis was done to determine the correlation of transcutaneous (forehead and sternal) bilirubin with serum bilirubin levels and assess the factors affecting transcutaneous bilirubin measurement. Results: In the range of serum bilirubin concentrations till 15 mg/ dl, a close correlation was observed between serum bilirubin (TSB) estimated by direct spectrophotometric method and transcutaneous bilirubin (TcB) estimated by “Bilitest 2000”. TcB estimation on the sternum was better correlated than that on the forehead (r-value: 0.962 vs. 0.935). TcB had a good correlation with TSB across the range of 12.5 - 20.5 mg/dl. Neonatal hypothermia significantly decreased TcB estimation (p =0.021, F=4.227). Respiratory distress, convulsion, sclerema and shock in neonates did not affect TcB estimation. Conclusion: TcB has a good correlation with TSB in term and late preterm neonates. Thus TcB readings can be used to screen and manage neonatal hyperbilirubinemia cases. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 690-697